Energetic Costs of AhR Activation in Rainbow Trout (Oncorhynchus mykiss) Hepatocytes - Nault, Rance (Université d'Ottawa / University of Ottawa, 2011)
Aquatic organisms in response to toxic insults from environmental pollutants activate defence systems including the aryl hydrocarbon receptor (AhR) in an attempt to metabolize and excrete these toxicants and their metabolites. These detoxification mechanisms however may come with certain energetic costs. I hypothesize that the activation of the AhR by β-Naphthoflavone (β-NF), a model AhR agonist, results in increased energetic costs requiring metabolic reorganization in rainbow trout hepatocytes. While the results obtained suggest that there are no significant energetic costs of AhR activation, analysis of enzyme activities suggests possible metabolic reorganization. This study also showed significant changes in cellular processes in hepatocytes over the incubation periods which previously were not reported. Furthermore, for the first time in fish hepatocytes, metabolic flux analysis (MFA) was used to examine intra-cellular metabolism, the applicability of which is discussed.
Keywords: rainbow trout; hepatocytes; detoxification; aryl hydrocarbon receptor; energetic costs; metabolic flux analysis